2019
DOI: 10.1200/jco.19.00640
|View full text |Cite
|
Sign up to set email alerts
|

MARS: Mutation-Adjusted Risk Score for Advanced Systemic Mastocytosis

Abstract: PURPOSE To develop a risk score for patients with advanced systemic mastocytosis (AdvSM) that integrates clinical and mutation characteristics. PATIENTS AND METHODS The study included 383 patients with AdvSM from the German Registry on Disorders of Eosinophils and Mast Cells (training set; n = 231) and several centers for mastocytosis in the United States and Europe, all within the European Competence Network on Mastocytosis (validation set; n = 152). A Cox multivariable model was used to select variables that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(132 citation statements)
references
References 25 publications
1
130
0
1
Order By: Relevance
“…Interestingly, recent human studies have highlighted an association between allergic disease and anemia [30][31][32]. Further, it is well established that patients suffering from mastocytosis also present with severe anemia [33,34]. Although several plausible explanations have been proposed to explain these associations, including the possibility that mast cell-derived effector molecules kill erythrocytes, it is possible that they might be the result of a defective development branch point that forces the overabundance of mast cells to the detriment of erythrocytes.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Interestingly, recent human studies have highlighted an association between allergic disease and anemia [30][31][32]. Further, it is well established that patients suffering from mastocytosis also present with severe anemia [33,34]. Although several plausible explanations have been proposed to explain these associations, including the possibility that mast cell-derived effector molecules kill erythrocytes, it is possible that they might be the result of a defective development branch point that forces the overabundance of mast cells to the detriment of erythrocytes.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Combination therapies with midostaurin and allogenic HSCT in eligible candidates should be considered for these patients. 9 …”
mentioning
confidence: 99%
“…Recent studies have shown that in >60% of all patients with advanced SM (ASM, SM-AHN or MCL), neoplastic cells harbor somatic variants in relevant genes other than KIT [ 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. These additional mutations affect genes encoding transcription factors (e.g., RUNX1 ), signaling molecules ( JAK , KRAS , NRAS , CBL ), epigenetic regulators ( TET2 , ASXL1 , DNMT3A , EZH2 ) or splicing factors ( SRSF2 , SF3B1 , U2AF1 ).…”
Section: Role Of Additional Genetic Variants (Mutations) As Drivermentioning
confidence: 99%